2019
DOI: 10.1080/13674676.2019.1623767
|View full text |Cite
|
Sign up to set email alerts
|

Breaking up with Jesus: a phenomenological exploration of the experience of deconversion from an Evangelical Christian faith to Atheism

Abstract: This study examines the experience of deconversion from an Evangelical Christian faith to Atheism in the UK. Semi-structured interviews were conducted with six participants and the data were analysed using Interpretative Phenomenological Analysis. The resulting superordinate themes emerged: Process of Deconversion; Post Deconversion Issues; What Helped and Did Not Help. The findings are supportive of similar research conducted on deconversion but are from a UK, rather than from a largely American, perspective.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…This would be the prediction on the basis of the set-point theory (Lykken, 1999) and its variants. Many of the 25 former Protestant ministers whom Lee (2015) interviewed reported that shortly after the disaffiliation there was a decline in happiness and well-being, probably due to tension in familial and social relationships. However, as time went by, a heightened sense of intellectual freedom, peace, empowerment, and autonomy developed.…”
Section: Can Both Be True?mentioning
confidence: 99%
“…This would be the prediction on the basis of the set-point theory (Lykken, 1999) and its variants. Many of the 25 former Protestant ministers whom Lee (2015) interviewed reported that shortly after the disaffiliation there was a decline in happiness and well-being, probably due to tension in familial and social relationships. However, as time went by, a heightened sense of intellectual freedom, peace, empowerment, and autonomy developed.…”
Section: Can Both Be True?mentioning
confidence: 99%
“…Current literature is heavily skewed towards exit from Christian traditions. Of the studies describing narratives of religious exit that were utilized for this synthesis, almost half focused on exiters of HC3 Christian groups (Babinski, 1995; Coates, 2010; Collins, 2016; Fazzino, 2014; Gillette, 2015; Gull, 2022; Ineichen, 2019; Lee & Gubi, 2019; Lougheed, 2015; Nica, 2018; Smull, 2002). The data are also geographically biased; most of these narratives came from the United States (however, this paper also incorporates studies from Israel, the United Kingdom, Germany, Italy, the Netherlands, Canada, and Australia).…”
Section: Religious Exit and Mental Healthmentioning
confidence: 99%
“…Many can point to a specific moment when their self‐concept and the religious role they occupied became incompatible. They view that moment as a “breakthrough” (Babinski, 1995, p. 187), “the straw that broke the camel's back” (Babinski, 1995, p. 122), or the “final crack” (Lee & Gubi, 2019, p. 175). One interviewee provided a striking visual metaphor – “it's like you're riding down a slope and you see ahead of you that the path splits into two and you have time, but you have to choose” (Davidman & Greil, 2007, p. 210).…”
Section: Religious Exit and Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the circumstances of the months that have followed your death, it seems longer ago than January 2020. From the outpouring of other's grief presented by media outlets after your helicopter crash, you remain a public figure of profound dissonance, a spiritual dissonance, or tension of contrasting pulls that resonate in ways that are much more than "cognitive" alone (Lee & Gubi, 2019;Price-Spratlen, 2015). You resonate with emotion and belief, in who I/we understood you to be, and most vitally, who you were becoming.…”
Section: Dear Kobementioning
confidence: 99%